1987
DOI: 10.1007/bf02833598
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia: Key factor in the pathogenesis of hepatic encephalopathy

Abstract: There is substantial clinical and experimental evidence to suggest that ammonia toxicity is a major factor in the pathogenesis of hepatic encephalopathy associated with subacute and chronic liver disease. Ammonia levels in patients with severe liver disease are frequently found to be elevated both in blood and cerebrospinal fluid (csf). Hepatic encephalopathy results in neuropathological damage of a similar nature (Alzheimer type II astrocytosis) to that found in patients with congenital hyperammonemia resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
1
8

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(195 citation statements)
references
References 22 publications
10
175
1
8
Order By: Relevance
“…42 The most prominent neuropathologic feature of HE is the alteration of astrocyte morphology and function. 2,43,44 Therefore, it may be speculated that the present findings may be partly related to the changes in astrocyte characteristics. Further studies are necessary to assess this possibility.…”
Section: Discussionmentioning
confidence: 82%
“…42 The most prominent neuropathologic feature of HE is the alteration of astrocyte morphology and function. 2,43,44 Therefore, it may be speculated that the present findings may be partly related to the changes in astrocyte characteristics. Further studies are necessary to assess this possibility.…”
Section: Discussionmentioning
confidence: 82%
“…There are also similarities between the neuropathologic lesions observed in the brains of monkeys and humans intoxicated with manganese (Yamada et al, 1996) and the brains of cirrhotic patients who died with hepatic encephalopathy (Butterworth et al, 1987); Alzheimer type II changes have been observed in both circumstances and were predominant present in basal ganglia.…”
Section: Relationship Between Brain Manganese Accumulation and Neurolmentioning
confidence: 79%
“…8 These observations are in agreement with the fact that cerebral edema is a consequence of hyperammonemia. 2,9,10 Indeed, the cause of astrocyte edema is unknown but it could reflect the osmotic effect of accumulated intracellular glutamine which is the primary metabolic product of ammonia metabolism in the brain. 1 Glutamine synthetase, which is responsible for this, is located in astrocytes.…”
Section: Discussionmentioning
confidence: 99%